SALING PERAN ANTARA BUDGETING, DINAMIKA LINGKUNGAN BISNIS, DAN KONFLIK INTERNAL: STUDI INTERPRETIF - Sujoko Efferin; Arthur Handrian (Journal of Management and Business, 2010)
Business has various interesting problems for academic research. Professionals needs to have reliable planning and control activities to ensure the achievement of organisational objectives. However, the dynamics of business environment also plays a significant role in determining the success or failure of the implementation of the planning and control. When organisation fails to achieve what has been planned due to environmental changes, internal conflicts are often unavoidable. This interpretive study examines the interplay between Budgeting, environmental dynamics and organisational conflicts to enrich the current literatures of Budgeting in Indonesian context.